1996
DOI: 10.1088/0953-2048/9/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgO addition on phase evolution and flux pinning of Bi-2212/Ag tapes fabricated by electrophoretic deposition and partial-melting processing

Abstract: MgO or SrSO 4 particulates were introduced into Bi-2212/Ag tapes during the fabrication process with the intention of producing flux pinning centres. It was found that (i) MgO or SrSO 4 normal particles added to Bi-2212 superconductor do not react chemically with or corrupt the Bi-2212 phase, but MgO may alter the phase evolution during the partial melting and the solidification of Bi-2212 and reduce the second-phase inclusions, (ii) MgO addition may enhance the flux pinning potential in a certain region of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…6 All these techniques use specific organic additives to obtain adequate slurry. The composition of this slurry depends on the requirements of the particular processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…6 All these techniques use specific organic additives to obtain adequate slurry. The composition of this slurry depends on the requirements of the particular processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…One striking feature of such materials is the existence of two superconductive transitions: a higher one at which the grains become superconducting but the matrix remains normal and a lower one at which the whole composite becomes superconducting but the critical current density is low. Another attractive feature is that the magnetic flux pinning and critical current density of superconducting composites are enhanced (Matsumoto et al, 1994;li Huang et al, 1996) at a low fraction of several non-superconductors. The most obvious application of these materials is to make a superconducting fault current limiter (SFCL) because composite superconductors have a broad range of current-carrying capacity (Mamalis et al, 2001).…”
Section: Compound Superconductorsmentioning
confidence: 99%
“…One of the common ways to increase J c 's of high temperature superconductors is addition of artificial flux pinning centres such as dispersed particles, defects or dislocation [1][2][3][4]. For Bi-2212 system, MgO particles incorporated into Bi-2212 matrix are good candidates for pinning centres since MgO is chemically inert with Bi-2212 at processing temperatures [3,4,[5][6][7][8][9][10]. It was also found that MgO addition into Bi-2212 bulk could improve texturing [4] and reduce the amount of the secondary phases in Bi-2212 thick films [3].…”
Section: Introductionmentioning
confidence: 99%
“…If the size of these particles is much greater than the coherence length of high temperature superconductors, particles cannot serve as pinning centres themselves. In this case, it is believed [3], that the extra pinning centres must be the interface between the MgO particles and the superconductor matrix. Bhargava et al [10] showed that the level of improvement of J c in Bi-2212/Ag thick films varied for samples with MgO particles of different origin and morphology; the best results were obtained for MgO particles of sharp cubic or prismatic shapes.…”
Section: Introductionmentioning
confidence: 99%